S64 Alveolar epithelial type II cell expression of VEGF-Axxxa is critical for development of Idiopathic Pulmonary Fibrosis (IPF): an anti-fibrotic role for VEGF-Axxxb anti-angiogenic isoforms?. (12th November 2015) - Barratt, SL; Blythe, T; Jarrett, C; Ourradi, K; Welsh, GI; Scotton, C; Bates, DO; Millar, AB
Abstract : Introduction: VEGF has been implicated in the development of IPF. Alternative splicing of the VEGF-A gene generates numerous isoforms. The differential effects of these isoforms, in particular the VEGF-Axxx b family, thought to have several opposing functions to the conventional family of isoforms (VEGF-Axxx a), have not been considered. Hypothesis: The balance of VEGF-Axxx a:VEGF-Axxx b isoform expression is important in the pathogenesis of IPF. VEGF-Axxx b isoforms may be protective against the formation of pulmonary fibrosis (PF). Methods: Normal and IPF lung lysates (n = 5) were analysed by western blotting (WB), and ELISA using an antibodies specific for PanVEGF-A and VEGF-Axxx b isoforms. The Bleomycin (BLM)-induced model of PF was used in conjunction with two transgenic (TG) mouse models, developed to explore the role of ATII-derived VEGF in the development of PF: 1) a conditionally inducible, ATII-specific, VEGF knock-out mouse (STCLL mice) and 2) a TG mouse over-expressing VEGF-Axxx b in ATII cells (MMTV-VEGF165 b). To explore the therapeutic potential of VEGF-Axxx b in PF, wild-type mice were administered intraperitoneal (IP) injections of VEGF-A165 b, commencing 10 days after BLM challenge. In all experiments fibrosis was assessed histologically using Masson's Trichrome, with blinded scoring of tissue sections. Results: By WB (n = 3) and ELISA (n = 5) there was no significant difference in PanVEGF-A expression between normal and IPF lung homogenates ( t -test, p > 0.05). In contrast, VEGF-Axxx b expression was significantly increased in these same IPF samples compared to control, by ELISA ( t -test, ****p < 0.0001) and WB (Densitometry: t -test, *p < 0.05). Specific deletion of VEGF-A from ATII cells of mice ameliorated the development of BLM-induced pulmonary fibrosis (n = 5, Lung fibrosis score: ANOVA with Holm's Sidak **p < 0.01). Over-expression of VEGF-Axxx b in ATII cells also ameliorated the development of pulmonary fibrosis (n = 6, Lung fibrosis score: ANOVA with Holm's Sidak ***p < 0.001). Furthermore, delivery of VEGF-A165 b, specifically during the fibrotic phase of the BLM model, also attenuated lung fibrosis development (n = 6, Lung fibrosis score: ANOVA with Holm's Sidak *p < 0.05). Conclusion: Changes in the bioavailability of ATII cell-derived VEGF-A, namely the ratio of VEGF-Axxx a:VEGF-Axxx b, appear critical to the development of pulmonary fibrosis. This data suggests that more a targeted approach to anti-VEGF-A therapy in IPF should be explored.